Analysis of Inventory Problems Using the Fault Tree Analysis Method (Case Study: PT Kimpai Dyna Tube) - Siti Salwa Azzahra Nurazizah Nuruljannah; Ratna Dewi Kusumaningtyas; Tyas Samesti (OPSI, 2022)
PT Kimpai Dyna Tube focuses on PBL (Plastic Barier Laminate) Tube products, which currently focuses on providing cosmetic products with plastic-based materials. Based on the results of the field survey on the inventory process, several problems were found, namely overstock material, deadstock material and outstanding material. The analysis process used is the Fault Tree Analysis (FTA) method because of its efficiency. Based on the results of the FTA, it was found that the basic event in the case of overstock material and deadstock material, namely changes in skincare trends in the community that caused very significant changes in the results of purchase orders and forecasts. The solution for the problem of overstock material and material deadstock is the application of a stock level system on inventory. Meanwhile, in the Outstanding material case, 3 basic events were obtained including, long lead time for delivery by overseas suppliers, trouble machines and many rejected quality items. Based on the results of the FTA, solutions were found for these problems, including performing careful calculations for the process of purchasing goods from foreign suppliers, providing machine spare parts and coordinating with suppliers and customers regarding the quality standards of production.